Cartography: Sciences, Art and Technology - Farika Nikmah; Erlangga Andi Sukma; Evi Suwarni (Budapest International Research and Critics University, 2022)
This research was conducted because of the different views on cartography, both from the point of view of benefits as well as the disciplines that cover it. Cartography paradigm shift that cartography is not a rigid work that is only understood by certain circles but as an attractive and communicative map that is understood by the community.: to describe modern cartography with a blend of science, art and technology. using a literature review, with a qualitative research approach. Modern cartography is a map produced from careful observation and analysis, using methods according to the right rules, presented in an attractive manner for the long-term interest, by utilizing the latest technology, serving and focusing on user needs. Today, most agree that maps are said to be good if they follow civilization, can provide broad benefits and are not a rigid result, but can be a source of information that can be used by individuals and organizations.